Culture, emotions and narratives in education for cultural diversity: A sociocultural approach - Muller Mirza Nathalie (Psihologija, 2016)
Developing a reflexive stance on personal emotions and experiences relating to otherness is one of the main goals of innovative pedagogical activities designed to combat racism. This novel socio-constructivist approach to cultural diversity in education seems an interesting alternative to essentialist approaches, as it involves the learner and uses reflexivity to foster change. However, little is yet known about the psychosocial effects of introducing emotions and personal experiences into the learning environment. In this paper, adopting a sociocultural theoretical framework, we describe two pedagogical settings in which students’ emotions and personal experiences were addressed in a multicultural context. The results of our first study showed that, in some teacher-student interactions, students’ verbalized emotions were articulated in a more generic discourse. Working with emotions can therefore lead to what we call a secondarization process, whereby personal experiences are related to collective and conceptualized knowledge. However, these pedagogical practices may also generate unexpected outcomes that hinder learning. The second study explored the structuring effect of (self-)narratives, viewed as psychological instruments. These findings are discussed with a view to informing the debate on the role of emotional aspects in education, and sociocultural research in psychology examining the complex interplay between individual and cultural dimensions in learning.